Our beautiful moon and its mysterious magnetism : a long voyage of discovery - Fuller, Mike (SpringerBriefs in Earth Sciences,, 2014)
This book is a summary of the history of discovering the moon. The author has been involved in the Apollo program, working with its samples and this book covers these efforts. It describes the analysis methods of lunar samples and their interpretation to understand lunar paleomagnetism. The book has adopted an historical approach throughout, tracing the development of the ideas of the Earth-moon system, of the birth of the space age, of paleomagnetism and finally of lunar magnetism and its evidence for an early lunar dynamo.